Opportunities for redistributed manufacturing and digital intelligence as enablers of a circular economy. Issue 2 (4th March 2019) - Moreno, Mariale; Court, Richard; Wright, Matt; Charnley, Fiona
ABSTRACT: The linear production of consumer goods is characterised by mass manufacture by multinational enterprises and globally dispersed supply chains. The current centralised model has created a distance between the manufacturer and end user, limiting the opportunity for intelligent circular approaches for production and consumption. Through a mixed method approach, opportunities of circularity are explored for the consumer goods sector. The study presents four lenses to analyse three enterprises through a multi-case study approach to explore the potential of digital intelligence and redistributed manufacturing (RDM) as enablers of circular business models. In addition, the study examines whether Discrete Event Simulation can be used to evaluate the circular scenarios identified through quantifying flows of material that determine traditional economic value (cost/tonne). The mixed method approach demonstrates that, a qualitative systemic analysis can reveal opportunities for circularity, gained through implementing 'digital intelligence' and distributed models of production and consumption. Furthermore, simulations can provide a quantified evaluation on the effects of introducing circular activities across a supply chain.